2020
DOI: 10.21053/ceo.2019.01298
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Photopenia on 18F-Fluorodeoxyglucose Positron Emission Tomography-Computed Tomography Scans Predicts Poor Prognosis in Nasopharyngeal Cancer Patients Undergoing Concurrent Chemoradiotherapy

Abstract: Objectives. To investigate the influence of pretreatment primary tumor or nodal photopenia (PP) on <sup>18</sup>F-fluorodeoxyglucose positron emission tomography-computed tomography (FDG PET-CT), an indicator of tumor ischemia, on survival results of nasopharyngeal cancers (NPCs) treated with concurrent chemoradiotherapy (C-CRT).Methods. The pre-C-CRT FDG PET-CT scans of 104 patients with NPC (cT1-4 N0-3 M0) were retrospectively examined to determine the presence of PP (PP+). Our primary endpoint w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Many studies have shown that the higher SUVmax, MTV, and TLG values are associated with worse treatment outcomes (10). There are few studies showing the meaning of parameters derived from PET for locally advanced NPC patients (11)(12)(13). More studies that evaluate the significance of PET-derived parameters concerning disease prognosis are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the higher SUVmax, MTV, and TLG values are associated with worse treatment outcomes (10). There are few studies showing the meaning of parameters derived from PET for locally advanced NPC patients (11)(12)(13). More studies that evaluate the significance of PET-derived parameters concerning disease prognosis are needed.…”
Section: Introductionmentioning
confidence: 99%